Enhancing Theatrical Makeup Competency through Project-Based Learning, Tutorial Videos, and Adaptive Learning Styles - Yupelmi, Mimi; Ambiyar; Nizwardi Jalinus; Chairani, Vici Syahril; Suci, Puji Hujria; Saputra, Indra (Journal for Lesson and Learning Studies, 2024)
The competency of theatrical makeup is indispensable in the digital learning era, however achieving theatrical makeup competency is still facing barriers and challenges. This research aims to analyze variables influencing theatrical makeup competency achievement. A quantitative survey used as a research method and questionnaire used for collecting data. Respondents are 105 students of Makeup and Beauty Department. Data was analyzed using Structural Equation Model-Partial Least Square (SEM-PLS) with Smart PLS 4.0 software. The prerequisite analysis describe that the measurement model is valid and reliable. Study result describe that project-based learning has a positive and significant impact on theatrical makeup competency with the high effect category. Furthermore, tutorial videos exhibit a positive yet insignificant impact on theatrical makeup competency with low-effect category. Additionally, learning style has a positive and significant effect on theatrical makeup competency with the high-effect range. Learning style as mediator variable performs full mediation in both variable correlations. This result provides alternative factors supporting competency achievement.